Conceptualizing cyberspace through the representation of paranoia in Thomas Pynchon’s Gravity’s Rainbow and The Crying of Lot 49 - Clarke-Fisher, Bradley William (https://orcid.org/0009-0005-2511-4367) (Rhodes University, 2026)
This thesis argues that postmodern subjectivity is fundamentally defined by its relationship with information technology, a relationship that generates a particularly paranoid subjectivity. This paranoia arises from the subject’s disorientation within the digital landscape of postmodernity, characterized by an overwhelming influx of information, hidden structures of control, and the destabilization of traditional epistemologies and structures of meaning. This condition is prefigured in the literary works of Thomas Pynchon, particularly The Crying of Lot 49 and Gravity’s Rainbow, where he represents paranoia as emerging as a response to the overdetermination of bureaucratic apparatuses of surveillance and control, enabled and intensified by technology, in postindustrial society. By analyzing Pynchon's representations of bureaucratic networks, I draw a comparison and note a similarity between the fictional environments of his novels and the contemporary digital sphere, particularly the Internet and social media platforms, which can be argued to function as analogous systems of control and surveillance. These platforms, underpinned by algorithmic logic and decentralized infrastructures, produce a sense of epistemic instability that mirrors the paranoid logic Pynchon's characters adopt in their efforts to find coherence within the complex systems they find themselves enmeshed in. I consider how postmodern subjectivity has been shaped by shifts from Enlightenment models of rational agency to post-structuralist and postmodern understandings of the self as fragmented. Drawing on theorists such as Karl Marx, Louis Althusser, Michel Foucault, Jean-François Lyotard, Slavoj Žižek, Jürgen Habermas, and Fredric Jameson, the convergence of global capitalism and cyberspace has created a disorienting social infrastructure in which meaning becomes unstable, and subjectivity becomes increasingly mediated by systems of surveillance and commodified information. I conclude that the rise of conspiratorial logic in the digital age represents not only a symptom of epistemic crisis, but also a survival mechanism: a way for subjects to orient themselves amid the erosion of traditional institutions of knowledge and legitimacy. In this context, Pynchon's paranoid characters provide an analogy of how contemporary individuals navigate the complexity of digital postmodernity, through the only organizational principle that remains feasible in a fragmented and algorithmically driven content economy: conspiratorial logic.
Keywords: Paranoia in literature (http://id.loc.gov/authorities/subjects/sh94007529); Pynchon, Thomas (http://id.loc.gov/authorities/names/n79099184); Postmodernism (Literature) (http://id.loc.gov/authorities/subjects/sh89000478); Cyberspace (http://id.loc.gov/authorities/subjects/sh97002963); Conspiracy in literature (http://id.loc.gov/authorities/subjects/sh2008000921); Critical theory (http://id.loc.gov/authorities/subjects/sh88002456); Poststructuralism (http://id.loc.gov/authorities/subjects/sh97005237); Internet in literature (http://id.loc.gov/authorities/subjects/sh2009002818); English; Late capitalism (https://www.wikidata.org/wiki/Q1423189)